The Eﬀect of Erythrocyte-Containing Donor Blood Components in the Priming of the Cardiopulmonary Bypass Circuit on the Development of Systemic Inﬂammation During Correction of Congenital Heart Defects in Children - D. V. Borisenko; A. A. Ivkin; D. L. Shukevich; R. A. Kornelyuk (Общая реаниматология)
Various pathological factors accompanying any cardiac surgery can cause intraoperative systemic inﬂammatory responses (SIR). As the number of cardiac surgical interventions grows worldwide, the issue of SIR prevention appears highly relevant.Aim of the study. To determine the eﬀect of not using donor blood components in the priming of the cardiopulmonary bypass circuit in children with septal congenital heart defects, operated under cardiopulmonary bypass, on the severity of SIR.Material and methods. A prospective, randomized study included 40 children with a median age of 14 [12–22.5] months and weight of 8.8 [7.25–11] kg. All patients underwent radical correction of septal defect under cardiopulmonary bypass. The patients were divided into two groups depending on the use of donor blood components for priming the CPB. The severity of SIR was assessed using four speciﬁc serum biomarkers such as interleukin 1b (IL-1b), interleukin 6 (IL-6), interleukin 10 (IL-10), and tumor necrosis factor alpha (TNF-α), measured before the operation, after the CPB and 16 hours after the surgery. In addition, the intra- and postoperative periods were evaluated.Results. The safety of the proposed strategy of skipping the donor blood was confirmed by lack of any organ dysfunction in all patients, as well as a significant difference in the balance of oxygen delivery and consumption. In addition, the levels of systemic inflammation markers after CPB were significantly higher in patients who had transfusion: IL-1b was 3.3 [3.2–3.48] pg/mL vs 2.86 [2.7–3.11] pg/mL (P=0.003) and TNF-α reached 1.81 [1.37–3.3] pg/mL vs 1.33 [1.26–1.76] pg/mL (P=0.034). Meanwhile, 16 hours post surgery, IL-6 and IL-10 levels were significantly higher in the group using donor blood components with IL-6 being 48.91 [33.89–57.6] pg/mL vs 31.56 [26.83–48.89] pg/mL (P=0.087) and IL-10 reaching 0.8 [0.76–1.43] pg/mL vs 0.69 [0.6–0.83] pg/mL (P=0.005).Conclusion. The study demonstrates and conﬁrms the safety and eﬃcacy of cardiopulmonary bypass without using donor blood components to reduce the severity of the systemic inﬂammatory response in children undergoing correction of septal congenital heart defects.